Externalizing Behaviour in Macao: Gender and Parental Participation - Kuok, Oi Lou (University of Saint Joseph, 2023)
There are gaps in the research on gender differences and parental participation and the interaction between gender and parental participation in non-Western cultural contexts, particularly the Macao context. The current study aims to fill these gaps by examining gender and parental participation (i.e., father only, mother only, or both) differences and interactions in externalizing behaviour (oppositional defiant disorder and conduct disorder) during late childhood and adolescence (i.e., from age 10 to 18) in Macao. The methodological approach for the current study was a cross-sectional design with a quantitative methodology based on self-rated questionnaires. In certain items, we did discover gender differences. More boys than girls appeared to concur that they occasionally misbehave at school or start fires. And it appeared that girls were more likely than boys to concur that they occasionally exhibit unexpected mood or emotion changes and strong tempers. The children in the groups where only the mother or father participated tended to agree more than they prefer to hang out with older kids than kids their own age. This is in contrast to the group with more parental participation, which is represented by both parents submitting the questionnaire. Although none of the hypotheses proposed were supported, our outcomes implied culture and subculture may play important roles on youths’ externalizing behaviour
Keywords: Externalizing behaviour; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; gender; parental participation

Gender Differentiated Parenting and Family Characteristics Affecting Parent-Adolescent Relationship in Macao: Che Iok Seng a.k.a Matthew - Che, Iok Seng (University of Saint Joseph, 2023)
This study aims to investigate gender-differentiated parenting and the factors that affect parent-adolescent relationships in Macao families. The study will address the following research questions: A) Does gender-differentiated parenting exist in Macao families? B) How does the academic level of parents relate to conflict resolution and acceptance levels? C) How does the length of time parents have lived together relate to conflict resolution and acceptance levels? D) How does the sibling position of adolescents relate to conflict resolution and acceptance levels? The study employed a quantitative research approach with a purposive and convenient sample of parents with children aged between 12 to 18 years old in Macao. The data were collected using the Parent-Child Interaction Questionnaire—Revised-Parent version (PACHIQ-R-P) through a questionnaire survey from May to August 2022. Out of the 172 completed questionnaires, seven were invalid, resulting in 165 valid questionnaires. The findings showed that gender differentiation in parenting was confirmed, with significant results showing that fathers had lower acceptance and conflict resolution levels when their child was a boy. Mothers showed similar acceptance and conflict resolution levels regardless of their child's gender. Furthermore, the study found that parents' acceptance of their children was influenced by their academic level, length of time living together, and the child's sibling position. This study is the first of its kind in Macao and could provide valuable insights for family and adolescent services in the region
Keywords: Adolescents; Conflict Resolution; Gender differences; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

The Effect of Empathy on Relationship Satisfaction in Young Adult Lovers in Macau: The Role of Love Maintenance Behaviors - 黎志濠 (University of Saint Joseph, 2024)
The purpose of this study was to explore the correlation between empathy, love maintenance behaviors, relationship satisfaction in a convenience sample of young adult lovers in Macau. Participants were N = 183 (84 males, 99 females) recruited from the social media platform (e.g. Instagram, WeChat, Facebook). Firstly, young adult lovers who tended to have high relationship satisfaction and empathy are tended to use positive love maintenance behaviors but less likely to use negative love maintenance behaviors. Besides, there were differences found by gender in empathy (affective empathy & total empathy), some dimensions of positive love maintenance behaviors (openness & advice), and negative love maintenance behaviors (causing jealousy, destructive conflict & negative love maintenance behaviors in general). Lastly, the findings in this study supported the hypotheses that love maintenance behaviors mediated the relationship between relationship satisfaction and empathy among young adult lovers in Macau. It was revealed that there was higher satisfaction in younger adult lovers in younger group (18-24 years) compared to older groups (32-40 years). For empathy, it correlated positively with relationship satisfaction and most positive love maintenance behaviors, but also with certain negative love maintenance behaviors. Positive love maintenance behaviors mediate the relationship between relationship satisfaction and empathy, highlighting their critical role in maintaining healthy relationships
Keywords: Love maintenance behaviors; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; empathy; relationship satisfaction

THE RELATIONSHIP BETWEEN PARENTING STYLES, ACADEMIC ACHIEVEMENT AND BEHAVIORAL PROBLEMS OF PRIMARY STUDENTS IN MACAO - Tang, I. Sam (University of Saint Joseph, 2023)
"Parenting styles may have various effects on children’s development and educational outcomes, particularly a relationship with behavioral problems and academic achievement. This study examines the relationship of between parenting styles, behavioral problems and academic achievement. A cross-sectional and questionnaire-design (Parenting Style Scale (Saunders et al., 2013); Strength and Difficulties Questionnaire (Goodman & Goodman, 2009; Goodman, 1999; Goodman, 1997)) study was used with a sample total of 98 parents with the eldest child of the family aged between six to twelve. Results of the findings are mainly inconsistent with the majority of literature. Indulgent and authoritative parenting are the predominant parenting styles, yet parenting styles does not relate to academic achievement. On the other hand, the correlation between behavioral problems, specifically prosocial behaviors and academic achievement are moderate. Furthermore, there is no difference between the type of behavioral problems according to gender. In further studies, a larger sample size, teachers and students as informants, and the inclusion of the analysis of other factors that could be influencing parenting styles, behavioral problems and academic achievement are suggested to be considered. "
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

THE RELATIONSHIP BETWEEN INTERNALISING PROBLEMS, ACADEMIC ACHIEVEMENT, SCHOOL ADAPTATION, AND GENDER, AS VIEWED FROM THE PERSPECTIVES OF BOTH TEACHERS AND STUDENTS - Ao, Hoi Ian (University of Saint Joseph, 2023)
The present study aimed to analyse the differences in the internalising problems (anxiety, depression, somatic complaints), assessed by different informants (teachers and students), according to the level of academic achievement and school adaptation level in secondary students. Furthermore, we examine the gender difference in the level of internalising symptoms. Finally, we analyzed the differences between teacher-rated and adolescents' self-reported internalising symptoms. The Achenbach System of Empirically Based Assessment (ASEBA) was used for collecting informants’ data. The sample consisted of 882 secondary students (349 males and 473 females), while 50 came from public schools and 772 from private schools. No significant differences are found in internalising problems according to the level of academic achievement from both teachers’ and students’ perspectives. Generally, students who are well-adapted to the school context have the least symptoms of internalising problems compared to average and less-adapted groups from the teachers' perspective. In addition, from students’ perspectives, adolescent females present more internalising problems than males. Finally, teachers rated fewer internalising problems when compared to the students. In conclusion, the low level of awareness of teachers towards the internalising problems of students arouse attention. It is suggested that teachers should attend professional development programs in order to address to students’ internalising problems
Keywords: Internalising problems; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; academic achievement; gender differences; school adaptation

EXPLORING THE IMPACTS ON MENTAL WELL-BEING OF UNIVERSITY STUDENTS UNDER COVID-19 PANDEMIC. A QUALITATIVE STUDY - Sit Chin Pok (University of Saint Joseph, 2024)
Coronavirus disease (COVID-19) is a public health emergency happening worldwide. It brought tremendous impacts to the global economy and people’s mental health (Jiaqi Xiong et al., 2020). Many people suffered physically and psychologically with the sudden arrival of COVID-19. Among the different age groups, studies identified that undergraduate students as a vulnerable group with a higher risk of mental health problems, such as depression and anxiety (Silva et al., 2022; King et al., 2022; Mansor & Ahmad, 2022). This qualitative study collected data from six focus group interviews with undergraduate students studying in Macao. Thematic analysis was used to understand the COVID-19 impact on students' mental well-being and coping strategies, as well as to explore the protective and risk factors that contribute to students’ mental well-being in the local context of Macao. Results showed four themes with 15 contributory sub-themes: COVID-19’s impact on students’ mental well-being, key impacting sources, coping strategies, and risk and protective factors. This study provides a picture of the mental health condition of undergraduate students during the zero-COVID period in Macao and raises an urgent call for extra attention to university students’ mental health during crises, showing the social and mental needs of undergraduates. This research also uniquely contributes insight into how the dysfunctionality of families could be a significant risk factor for students’ mental health during the crisis, which is rarely found in other COVID-19 studies. This research suggests a promotion of future programs or workshops that would strengthen and benefits students’ relationship with their family. Future research could explore the family function in Macao and its relationship with students’ mental well-being
Keywords: Mental Well-being; Qualitative; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); Undergraduate Student; University of Saint Joseph

SLEEP PROBLEMS IN MACAU CHILDREN AND ADOLESCENTS: ASSOCIATION WITH BEHAVIOURAL PROBLEMS AND ACADEMIC PERFORMANCE - Hio, Sam U. (University of Saint Joseph, 2024)
The adverse impact of sleep problems on children and adolescents’ health and development raises concern in the community. Although some studies have examined the association of sleep problems with behavioural problems and academic performance, few have been done in Macau, especially for the children population and regarding academic performance. Hence, the primary purpose of the present study was to identify sleep problems of children and adolescents in Macau and explore its relationship with behavioural problems and academic performance. 948 participants (466 children and 482 adolescents) from Macau were included in the study. Data was collected using the Achenbach System of Empirically Based Assessment (ASEBA) forms: CBCL, TRF and YSR. Children sleep problems were assessed by the reports of mother and father, in addition self-report was also included to measure adolescents sleep problems. Behavioural problems were reported by mother, father and teacher for children, as well as self-report for adolescents. Academic performance was the average of teacher’s rating of all academic subjects. The prevalence of sleep problems was 10.1% in children and 17.4% in adolescents. The results showed significant difference between children’s sleep problems and their mother and father-reported total behavioural problems, but not with teacher-reported total behavioural problems. However, whereas the t-test found that adolescent’s sleep problems significantly predicted all informants reported total behavioural problems, the chi-square test found no significant relationship between the two factors in teacher’s ratings, suggesting that while adolescents who had more sleep problems did show a higher frequency of total behavioural problems in the teacher’s perspective, but they may not be severe enough to be considered clinical. In addition, significant association between academic performance and sleep problems were only observed in children but not in adolescents; and no significant relationship was found between sleep problems and grade retention. Findings provided further support for some associations of sleep problems with behavioural problems and academic performance. In general, the findings of Macau were similar to those in other countries. Given that chronic sleep problems create multiple negative consequences to students’ lives, practical implications are provided to help lower it through the collaboration between parties, education about sleep hygiene and the development of healthy sleeping habits. Keywords: sleep problems; behavioural problems; academic performance; children; adolescents
Keywords: Macau; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; academic performance; adolescents; behavioural problems; sleep problems

COPING WITH WAR TRAUMATIC EXPERIENCES: CHRISTIAN AND MUSLIM PERSPECTIVES IN EAST TIMOR - Costa, Julieta da (University of Saint Joseph, 2024)
The researcher aims to understand how Christian and Muslim communities in East Timor cope with and recover from trauma arising from war, violence, and conflict. The research seeks to identify critical spiritual and religious coping mechanisms as present in East Timor (Timor Leste) that could help victims heal and reconstruct their lives after a war trauma experience. The study uses a mixed method, first deploying a quantitative investigation of Christian and Muslim communities in East Timor. The questionnaire aimsto understand how religion and spirituality feature in individuals' coping with trauma and the healing practices prescribed or encouraged by religious institutions and practices. In addition, a qualitative research and thematic analyses have been conducted and added with the facilitation of 6 Interviewees, 3 Muslims, and 3 Christians. This study aimed to investigate trauma levels and religious coping strategies among participants from East Timor. The quantitative findings indicated that the participants experienced a moderate level of trauma, with trouble sleeping being the most significant symptom. The qualitative findings revealed in some participants a high level of traumatic experiences. Recurrent thoughts of traumatic events and feeling jumpy were also prevalent. However, feeling strange around people or objects and feeling personally damaged by the trauma were less common. Regarding coping strategies, participants tended to rely on positive religious coping, seeking a stronger viii connection with God, finding comfort in religious communities and beliefs, and using spiritual interventions to manage emotions and worries, finding healing and a path toward the future. Both Catholics and Muslims employed positive religious coping strategies, with Catholics showing a slightly higher level in their utilization. However, the difference between the two groups was minimal. Positive coping strategies were more frequently used by participants from both religious backgrounds, highlighting their importance in dealing with trauma. Positive religious coping did not significantly impact trauma symptoms, showing no decrease or increase. However, a notable positive correlation existed between negative religious coping and more severe trauma symptoms. Individuals relying on negative coping strategies were more likely to experience heightened trauma symptoms. These findings align with previous research, emphasizing the positive association between Islamic appraisals and religious coping with better post-traumatic adjustment, while trauma-related appraisals are linked to worse adjustment. The study underscores the need to respect individual coping variations and recognizes the impact of negative religious coping on trauma experiences
Keywords: COPING STRATEGIES; COUNSELING; EAST-TIMOR; RELIGION; SPIRITUALITY; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; WAR

AI in Counselling: Perceptions on Human vs AI Generated Chat Counselling - Ieong, Ka U. (University of Saint Joseph, 2024)
The rapid development of counselling began after World War II. Meanwhile, texting services became available in the 1980s. Texting has been widely applied in both health area and mental health areas. A chatbot is a specific type of artificial intelligence (AI) that can have conversations with humans through texting. The combination of counselling and texting is known as chat counselling. The effectiveness of chatbots in alleviating psychological symptoms was supported by scientific research. Nonetheless, people hold different perceptions towards chatbots. Some common factors in counselling, including empathy and warmth, were also important in evaluating AI chatbots. Other important factors included acceptability, satisfaction and trust. The current study is the first to use AI as a counsellor. This study investigates people’s perceptions of human and AI counsellors (ChatGPT) and whether people can differentiate between human and AI. Participants needed to rate the counsellors in three scenarios: the original scenario taken from a training book, the human counsellor scenario generated from a text conversation with a human counsellor and the AI counsellor scenario produced by texting with ChatGPT, which acts as the counsellor. Prompts used to generate conversation with ChatGPT are included. The dialogues were parts of the conversations containing similar client responses and were presented using the WhatsApp interface. Questionnaires were delivered both online and in paper form. Results demonstrated that people’s ratings of human counsellors and AI counsellors did not differ in perceived empathy, acceptability, and satisfaction. While the warmth and trustworthiness of AI counsellors were perceived to be higher than those of human counsellors. On the other hand, people were unable to differentiate between human and AI counsellors in uncertain conditions. Younger people and the general population are more accurate in identifying between humans and AI, while people above 40 and psychologists or counsellors are less capable of doing so. The current study supports the potential of utilising ChatGPT in counselling. Having people experience and evaluate real chat counselling with human and AI counsellors can potentially eliminate some limitations of the current studies. Future studies can investigate how prior knowledge contributes to AI detection and examine AI counsellors' efficiency in longitudinal studies
Keywords: AI (Artificial Intelligence); Chat counselling; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; human perceptions

The Exploration of the Methadone Treatment Program in Heroin-Dependent: The Perspective from Users and the Quality of Life - Ma, Sara Vanessa (University of Saint Joseph, 2024)
This thesis explores the impact of the exploration of methadone treatment programs in heroin-dependent the perspective from use and the quality of life. The primary objective of this research is to investigate how different types of participants that methadone will affect their quality of life. A mixed-methods approach was employed, combining quantitative surveys with qualitative interviews to gather comprehensive data from a sample of 59 participants, 8 female, and 51 male, for the questionnaire to know about their quality of life and well-being. A structured questionnaire was used to quantitatively assess participants' quality of life, well-being, and satisfaction with methadone treatment. The survey included standardized scales measuring various dimensions of quality of life, such as physical health, mental health, social functioning, and overall life satisfaction. A mixed-methods approach was adopted, combining quantitative and qualitative research methods to provide a comprehensive understanding of treatment efficacy and genetic influences. In the course of this research on the impact of methadone treatment programs on the quality of life for heroin-dependent individuals, several key findings emerged from both the quantitative surveys and qualitative interviews. To overall improvement in quality of life the participants reported significant improvements in various dimensions of quality of life after starting methadone treatment. On average, scores for emotional well-being, social functioning, and physical health showed marked increases over the treatment period
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

TO EXPLORE SMOKING BEHAVIORS OF ADULTS IN MACAO: DISCOVERIES BY QUANTITATIVE AND QUALITATIVE STUDIES - Dias, Luis Borges (University of Saint Joseph, 2023)
The purpose of the study was to explore the smoking behaviour of the smokers living in Macao. I was part of the 1st group of doctors to have chosen to initiate smoking cessation in Macau. In addition to my diverse academic background of study in laws- a dissertation about the effect of tobacco control program in Macao (submitted in 2011), a master in Public Administration, and five years of working experiences as an Inspector Assistant of tobacco, I had the conviction that I have to write to share my experience and knowledge about smoking cessation to contribute to the field of counselling and psychotherapy as there is little research data concerning smoking prevalence and demographics in Macao. This study consists of two parts – PART I presents the quantitative data collected by a questionnaire-survey over 1378 smokers and PART II qualitative data from semi-structured interviews with 10 adult smokers to explore their experiences of smoking and smoking cessation in Macao. Quantitative data analysis was conducted with the SPSS, while qualitative analysis with coding and theme identification by following the grounded theory procedures. The study found that about 85% smoker surveyed consumed more than half a pack of cigarette per day and about 31% reported various symptoms like irritability, fatigue, loss of appetite and difficulties in concentration. The qualitative study has identified major positive factors related to initiation and maintenance of smoking cessation, namely health concerns, financial concerns and family support. Major negative factors related to relapse of smoking are peer influences, smoking of family members, and impacts of stressful life events. Based on findings of the study, it is argued that preventive anti-smoking education should be implemented among young people. Promotion of health education and preventive anti-smoking strategist and policy in Macao are discussed. The data collected indicate the fact that individuals who have pathologies of the cardiovascular system as a motivating factor for contemplating or taking actions for smoking cessation. Moreover, financial problems, gender (male predominantly), married with family support, higher educational level, without psychological diseases, better economic status, lower nicotine dependent are predictors to success in quit smoking. It also raises the possible need to deepen some evaluation parameters hither to be only superficially addressed. Therefore, and by limitations inherent to the study, this hypothesis needs further investigation. I argue that non-pharmacological treatment methods alone have proven to be effective in the smoking cessation process. However, it is argued that this combined with pharmacological therapy, in particular in specialized consultations, would be more effective and capable in increasing success rates in smoking cessation
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; grounded theory; relapse; smoking behaviour; smoking cessation

REMINISCENCE THERAPY IN INSTITUTIONALIZED ELDERLY PEOPLE: CASE STUDY = TERAPIA DE REMINISCÊNCIAS EM IDOSOS INSTITUCIONALIZADOS: ESTUDO DE CASO - Araújo, Filipa Maria Santos (University of Saint Joseph, 2024)
Keywords: Depression; Elderly; Mental Health; Reminiscence Therapy; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; Well-being

THE RELATIONSHIP BETWEEN PSYCHOPATHOLOGY AND RESILIENCE OF SECONDARY SCHOOL STUDENTS IN MACAO - Chan, Ngan Ieng (University of Saint Joseph, 2023)
School-age children and adolescents face several psychological conditions frequently associated with negative consequences on behavioral and mental problems. Their level of mental resilience may affect their responses to academic or interpersonal issues and coping with challenges, which in turn affects their mental health. This study aims to characterize the current status of the psychopathology and resilience of secondary students and to analyze the relationship between psychopathology and resilience in a sample of 80 girls aged 12–18 was selected by cluster sampling from one private secondary school with six grades in Macao. In this study, we used the Achenbach System of Empirically Based Assessment (ASEBA) to assess behavioral and emotional problems and the Resilience Scale for Chinese Adolescents to assess resilience. A total of 78 valid questionnaires were obtained for CBCL, 78 for TRF, 80 for YSR, and 77 for Resilience Scale and data were analyzed by using SPSS. The results reveal that clinical prevalence of Total Problems (YSR, 27.5% > CBCL, 19.2% > TRF, 15.4%) and Internalizing Problems (YSR, 22.5% > CBCL, 17.9% > TRF, 11.5%) from the perspective of adolescents was higher than that from the perspectives of parents and teachers. Senior students exhibited higher frequency on the borderline clinical range than Junior students. (χ2(2, N=80) =14.56, p<.001). The average score of resilience is 3.24±0.51, which is above the middle level. Regarding the YSR scale and Resilience scale, we found that the score of Affect Control is significantly negatively correlated with the score of Internalizing Problems (r = -.354, p<.01). Family Support is also significantly negatively correlated with the score of Internalizing Problems (r = -.302, p<.01). Good affect control and family support can reduce various emotional and behavioral problems. The results of the study found the resilience level can negatively affect internalizing problem behaviors and externalizing problem behaviors. The results are promising and can give clues for preventing and promoting measures regarding mental health issues to both family and school education contexts, as creating a sustainable development strategy of improving adolescents’ mental resilience quality
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph; psychopathology; resilience; secondary students

ASSESSING ADVERSE CHILDHOOD EXPERIENCE (ACEs) IN CHILDHOOD AND ADOLESCENT: TRANSLATION AND ADAPTATION OF ITEM-CA FOR CHINESE POPULATION IN MACAO - Lo, Antonio Man Ho (University of Saint Joseph, 2024)
Adverse Childhood Experiences (ACEs) are common in life trajectories, and continued exposure to childhood adversities has long-term consequences that can lead to lifelong physical, mental, and emotional deficiencies. This study aims to address the research gap in the ACEs context in Macao by enhancing our understanding of the cultural sensitivity, applicability, and acceptability associated with assessing ACEs among Chinese childhood and adolescents in Macao. The study utilized the Chinese version of The International Trauma Exposure Measure – Children and Adolescents (ITEM-CA) to facilitate the exploration of cultural adaptation needs related to ACEs measurement tools in Macao. Employing a qualitative methodology with an explanatory and descriptive design, the study collected opinions and suggestions through an online questionnaire from professionals working with children aged 7-17 years old, as well as parents or caregivers of children within the same age group. Several key findings emerged from the study. Firstly, it underscored the adequacy and pertinence of the Chinese ITEM-CA in covering the topics of traumatic events and deeming it more suitable for children aged 12 or above. Secondly, it emphasized the importance of maintaining anonymity and the involvement of dedicated and trained personnel throughout the ACEs assessment process. Lastly, it highlighted the need to increase public awareness regarding traumatic events and ACEs in Macao society. These findings have significant implications for researchers studying the prevalence of ACEs in Macao and for policymakers in Macao implementing ACEs surveillance. Additionally, there is a recommendation for organization, especially schools, to respond to ACEs using trauma-informed approaches, supporting the well-being of children, fostering resilience, and minimizing the risk of re-traumatization
Keywords: ACEs; Adolescent; Adverse Childhood Experiences; Chinese; ITEM-CA; Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph